Metabolite profiling of Christia vespertilionis leaf metabolome via molecular network approach - Norazhar, Anis Irfan; Lee, Soo Yee; Mohd Faudzi, Siti Munirah; Shaari, Khozirah (MDPI AG, 2021)
Christia vespertilionis (L.f.) Bakh. f. is an ornamental plant with unique butterfly-shaped leaves, hence its vernacular name “butterfly wing” or “rerama” in Malay. In Malaysia, the green-leafed variety of this plant has gained popularity in recent years due to testimonial reports by local consumers of its medicinal uses, which include treatment for cancer. Despite these popular uses, there is very limited information on the phytochemistry of the leaf of this plant, presenting a significant gap in the cheminformatics of the plant species. Herein, we report a substantially detailed phytochemical profile of the leaf metabolome of the green-leafed variety of C. vespertilionis, obtained by deploying an untargeted tandem mass spectrometry-based molecular networking approach. The detailed inspection of the molecular network map generated for the leaf metabolome enabled the putative identification of 60 metabolites, comprising 13 phenolic acids, 20 flavonoids, 2 benzyltetrahydroisoquinoline-type alkaloids, 4 hydroxyjasmonic acid derivatives, 2 phenethyl derivatives, 3 monoacylglycerols, 4 fatty acid amides, 2 chlorophyll derivatives, 4 carotenoids, 2 organic acids, 1 nucleoside, and 3 amino acids. Flavonoids are the major class of metabolites that characterize the plant leaves. Employing a mass-targeted isolation approach, two new derivatives of apigenin-6-C-β-glucoside, the major constituents of the plant leaf, were successfully purified and spectroscopically characterized as apigenin-6-C-β-glucoside 4′-O-α-apiofuranoside (28) and apigenin-6-C-β-[(4″,6″-O-dimalonyl)-glucoside] 4′-O-α-apiofuranoside (47). This work provides further information on the chemical space of the plant leaf,